SALING PENGERTIAN ANTAR DIALEK BAHASA KAILI DI LEMBAH PALU - Nur, Yunidar (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2010)
Mutual understanding among dialects is one of the aspects in research of comprehensive sociolinguistic. Assessment of mutual understanding shows how speakers from certain dialect or language society understand other dialect. This study focuses on examination of how far the speakers of four local dialect in Palu valley have interaction. These four dialects are Ledo, Da’a, Unde, and Rai. A sample of 20 people were surveyed representing each of four persons from society leaders, head of families, mothers, teenagers, and children. The results indicate that dialectal speakers of Ledo is 29,7%, Da'a is 37,26%, Unde is 40,14%, and Rai is 31,02% using Kaili language in various daily association domain. Congeniality to vernacular alone for adult circle is still very high. However younger people have less understanding of which there are about 80%. Difference mutual understanding between dialect interchangeably is not evident as shown by only 10% of the difference. Thus, it seems that there is good mutual understanding between speakers of four dialects of Kaili’s language. Ledo dialect seems to have higher level of understanding, this is not a suprising as Ledo is situated in the middle of the Palu Valley.